2010
DOI: 10.1007/s10694-010-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Fuel Moisture Thresholds in the Flammability of Calluna vulgaris

Abstract: Managed and wild fires play a significant role in the ecology of heathlands in the UK but we currently have little ability to forecast fire behaviour or the likelihood of accidental wildfires. Like many shrubland fuel types, heathlands display significant structural complexity and the role of different fuel components in governing flammability has not been clear. Using a series of small, field-based ignition tests, we demonstrate the critical importance of the moisture content of dead fine fuels in the lower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 26 publications
2
55
0
1
Order By: Relevance
“…FFMC, ISI and FWI perform substantially better than the other components overall in grassland and arable areas, most likely a result of quick-drying fine fuels dominating these land cover types during this season. A similar effect is observed in heath/bog/marsh environments; while deeper slow-drying peat layers may burn during drought conditions, most spring fires occur in the quick-drying canopies of heather stands (Davies and Legg, 2011). In coniferous -and to a lesser extent, broadleaved -environments, performance of the DMC and BUI components is high relative to performance in other land cover types, and in coniferous environments both DMC Fig.…”
Section: Evaluation Of the Fwi System Components By Land Cover Typesupporting
confidence: 53%
“…FFMC, ISI and FWI perform substantially better than the other components overall in grassland and arable areas, most likely a result of quick-drying fine fuels dominating these land cover types during this season. A similar effect is observed in heath/bog/marsh environments; while deeper slow-drying peat layers may burn during drought conditions, most spring fires occur in the quick-drying canopies of heather stands (Davies and Legg, 2011). In coniferous -and to a lesser extent, broadleaved -environments, performance of the DMC and BUI components is high relative to performance in other land cover types, and in coniferous environments both DMC Fig.…”
Section: Evaluation Of the Fwi System Components By Land Cover Typesupporting
confidence: 53%
“…MLR analysis was conducted to estimate MCI over the entire study area of Zaringol. Varimax1 and Varimax2 (Equations (1)-(4)) were used instead of the 13 and 5 variables as shown in MLR Equations (5)- (8). Out of a total of 32 samples, 77% of the data collected in the field were used to train the MLR model in the regression analysis, while the remaining 23% were used for validating the performance of the model.…”
Section: Multiple Linear Regression (Mlr)mentioning
confidence: 99%
“…Among the fuel moisture indices, LFMC has been widely used for fire danger studies [8,9] because it is not only simple to calculate but also the ignition delay and degree of flammability (the quantity of heat necessary to evaporate water) are correlated to the amount of water in live fuels [1]. In areas of high vegetation productivity, such as this study, a small reduction in fuel moisture may enhance the dry matter productivity (i.e., an increase in dead fuel load and connectivity) [10], and therefore fuel consumption is increased by fire.…”
Section: Introductionmentioning
confidence: 99%
“…Almoustafa et al (2009) have shown that fuel moisture in Calluna fell during the transition from spring to summer in their Peak District study area. Experiments by Davies & Legg (2010) have shown that fires spread rapidly through Callunadominated vegetation with moisture contents of less than 60% but fail to take hold above 70%. The rise in wildfires in spring and late summer also reflects the annual pattern of Easter and summer holidays, when more people visit the PDNP and so there are more possible ignition sources.…”
Section: Discussionmentioning
confidence: 99%